Life Cycle Assessment Industri Pangan Indonesia: Tinjauan Naratif - Priscilla Jasmine Kurniadi; Natalia Dwi Wulandari; Natania Faylinn Anggunjaya; Allegra Wijaya; Nurhayati (Indonesian Journal of Applied Technology, 2026)
This study conducted a narrative review of the application of LCA in the Indonesian food industry during the period 2020-2025. The types of products, boundary systems used, and environmental impacts in terms of global warming potential (GWP) or greenhouse emissions (GHE) were analyzed. Eleven articles were obtained from the Google Scholar database for further analysis. The results showed significant variations between products, such as tofu, tempeh, cane sugar, cocoa, and coffee, with varying emission values. The differences were due to energy sources, production scale, and analysis system boundaries (cradle-to-gate, gate-to-gate, cradle-to-grave). Industries that still use biomass or fossil fuels tend to produce higher emissions, while artisanal approaches and renewable energy sources show greater efficiency. In general, the majority of studies are still limited to the upstream production stages and do not cover the entire product life cycle. Therefore, it is necessary to expand the analysis towards cradle-to-grave and apply low-emission process innovations and circular economy principles to strengthen the transition to an environmentally sustainable food industry.